Video-Based Intelligent Traffic Control System - Zahari, Taha; Said Amir, Azan; Taufiq, Abdul Gani; Nazaruddin (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 14th - 15th May 2005 at Putra Palace Hotel, Kangar, Perlis.